(untitled) (Journal of European Studies (JES), 2024)
From the beginning of Ukraine’s independence in 1991, Crimean Tatars began effective political activity to restore their right to live in Crimea as indigenous people and to maintain a decisive role in Kyiv’s relations with the regional government of Crimea. Qurultay (representatives’ body) and Mejlis (executive body) were recreated to represent the Tatar people. The Mejlis adopted acts that did not have necessarily binding legal force, however, it was recognized and integrated into the Ukrainian legal system in 1999 through a presidential order. Policy recommendations of Mejlis were considered noteworthy in decisions made by Ukrainian authorities regarding issues of the Crimean Tatars particularly and Crimea in general. The focus of the paper is to study the transformation of Ukrainian supremacy in Crimea and the status of the Mejlis of the Crimean Tatar in pre- and post-2014. It is based on historical data on Crimean Tatars and analyses the legal acts and policies adopted by the highest authorities of Ukraine related to the subjects of the Mejlis. During the political events of ‘Euromaidan’ that took place in Ukraine in 2013-14 and the Russian annexation of Crimea through a referendum in 2014, the topic of the autonomy of the Crimean Tatars became a relevant issue of human rights and placed as a priority area in the agenda of the Ukrainian government. This research also serves as a case study of the minority group of displaced people who need someplace to stay and settle.